2014
DOI: 10.1002/prep.201400146
|View full text |Cite
|
Sign up to set email alerts
|

Curing of Glycidyl Azide Polymer (GAP) Diol Using Isocyanate, Isocyanate‐Free, Synchronous Dual, and Sequential Dual Curing Systems

Abstract: a] 1I ntroductionIn solid propellant rocketry,p ropulsion units in fielded and currently operational missile systems are founded upon ar elatively small number of firmly established propellant technologies, most of which have an extensive historical track record. While propulsion systems with either limited or no restrictions with respect to exhaust plume signature have their basis in ammonium perchlorate (AP) composites with inert binder systems (preferably aluminized), smokeless systems are based on nitrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 27 publications
0
41
0
Order By: Relevance
“…Among energetic polymers, glycidyl azide polymer (GAP) and related energetic polymer binders are considered as the most promising candidates for energetic binders in future composite solid propellants. GAP was first reported in a patent in 1972 by Vandenburg, and stands unchallenged among azide polymers prepared during the last few decades . This is because it has a high positive heat of formation (+957 kJ kg −1 ), low detonation tendency and low glass transition temperature ( T g = −45 °C) .…”
Section: Introductionmentioning
confidence: 99%
“…Among energetic polymers, glycidyl azide polymer (GAP) and related energetic polymer binders are considered as the most promising candidates for energetic binders in future composite solid propellants. GAP was first reported in a patent in 1972 by Vandenburg, and stands unchallenged among azide polymers prepared during the last few decades . This is because it has a high positive heat of formation (+957 kJ kg −1 ), low detonation tendency and low glass transition temperature ( T g = −45 °C) .…”
Section: Introductionmentioning
confidence: 99%
“…Results presented in Table 3 showed that tensile strength increases in the range 0.79 to 10.65 kgf cm -2 and Emodulus 0.70-42.53 kgf cm -2 . The trend in changing the mechanical properties of our studies has good agreement with data published by T. H Hagen et al [12]. This is due to while increasing curative ratio, enhances in crosslinking density of binder (GAP/BPHQ).…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…In addition, as the amount of BPHQ increases toughness of the cured polymer matrix also increases. As reported by T. H. Hagen et al [12], we could not observe any issues such as partial precipitation, and solubility during curing of GAP with BPHQ. The mechanical properties of a composite propellant can be modified by relative ratio of curative, proportion of solid fillers and adding plasticizer in appropriate quantity [20][21][22].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Among the energetic polymeric binders, glycidyl azide polymers (GAP) and their related energetic polymer binders are considered as promising candidates for propellant binders. 7,8 It is well known that GAP has a high positive heat of formation (+957 J g À1 ), low detonation tendency, low glass transition temperature (T g ¼ À45 C), and also has good compatibility with high-energy oxidizers. However, GAP which has high polarity azide groups graed on the polymer backbone, possesses poor exibility of backbone resulting in lack of intermolecular interactions, exhibits inferior mechanical properties in propellants formulations.…”
Section: Introductionmentioning
confidence: 99%